2017
DOI: 10.18632/oncotarget.18022
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant morphological structures in breast cancer represent transcriptionally distinct tumor cell populations with varied degrees of epithelial-mesenchymal transition and CD44+CD24- stemness

Abstract: Intratumor morphological heterogeneity in breast cancer is represented by different morphological structures (tubular, alveolar, solid, trabecular, and discrete) and contributes to poor prognosis; however, the mechanisms involved remain unclear. In this study, we performed 3D imaging, laser microdissection-assisted array comparative genomic hybridization and gene expression microarray analysis of different morphological structures and examined their association with the standard immunohistochemistry scorings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 47 publications
0
25
0
2
Order By: Relevance
“…Previously, we found that genes encoding ABC transporters are differentially expressed between various morphological structures [4]. Our resent study showed that different morphological structures represent transcriptionally distinct populations of tumor cells with varying degrees of epithelialmesenchymal transition and stemness [5]. Based on these results, we assumed that various morphological structures carry specific characteristics which modify chemotherapy efficiency.…”
Section: Different Morphological Structures Of Breast Tumors Demonstrmentioning
confidence: 78%
See 2 more Smart Citations
“…Previously, we found that genes encoding ABC transporters are differentially expressed between various morphological structures [4]. Our resent study showed that different morphological structures represent transcriptionally distinct populations of tumor cells with varying degrees of epithelialmesenchymal transition and stemness [5]. Based on these results, we assumed that various morphological structures carry specific characteristics which modify chemotherapy efficiency.…”
Section: Different Morphological Structures Of Breast Tumors Demonstrmentioning
confidence: 78%
“…1, b, c). In addition, the highly heterogeneous composition of these morphological structures [5] may contribute to drug resistance and should be considered when an appropriate chemotherapy regimen is chosen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В совместных исследованиях сотрудников НИИ онкологии Томского НИМЦ показаны различия характера распределения и фенотипического состава клеток воспалительного инфильтрата вокруг разных морфологических структур опухоли молочной железы. Морфологические структуры на основании их генетической и ýкспрессионной разнородности, установленной авторами, рассматриваются как функционально обособленные популяции опухолевых клеток, обладающих разным метастатическим потенциалом, в обеспечение которого очевидно могут вносить вклад и компоненты микроокружения [67][68][69][70].…”
Section: макрофаги и гетерогенность микроокруженияunclassified
“…Previously, we showed that breast tumor cells can be either single, arranged in small (discrete) groups, or arranged in more complex structures (tubular, alveolar, solid, and trabecular) (6). In addition, we suggested that the intratumor morphological heterogeneity in breast cancer is a result of the unfolding of the invasion program during which epithelial-mesenchymal transition (EMT) leads to significant morphogenetic changes in the tumor landscape: from tubular structures that are close to normal mammary ducts to discrete groups of tumor cells demonstrating a strongly pronounced mesenchymal phenotype (7). The recent study hypothesized that the intratumor morphological heterogeneity can be an attractive model for studying the mechanisms of collective cell invasion (by focusing on solid and trabecular structures) and individual cell invasion (by focusing on discrete groups, namely, STCs) (8).…”
Section: Introductionmentioning
confidence: 99%